GIS And Health : GISDATA 6. - Gattrell, A. (GISDATA., 1998)
An examination of appropriate methodologies for spatial analysis and spatial statistics in analyzing health data. The book explores the links with GIS and the problems associated with such analyses, and the statistical and cartographic methods for.